Deapioplatycodin D inhibits glioblastoma cell proliferation by inducing BNIP3L-mediated incomplete mitophagy - Yu Sun; Guangze Zhu; Renshuang Zhao; Yaru Li; Hongyang Li; Yunyun Liu; Ningyi Jin; Xiao Li; Yiquan Li; Tiemei Liu (Cancer Cell International)
Abstract Deapioplatycodin D (DPD) is a triterpenoid saponin natural compound isolated from the Chinese herb Platycodon grandiflorum that has antiviral and antitumor properties. This study aimed to investigate the effects of DPD on glioblastoma (GBM) cells and to determine its intrinsic mechanism of action. Using a CCK8 assay, it was found that DPD significantly inhibited the growth of GBM cells. DPD-treated GBM cells contained swollen and degenerated mitochondria with empty vesicular bilayer membrane-like autophagic vesicle structures in the periphery of the mitochondria under transmission electron microscopy. DPD activated autophagy in GBM cells and induced a blockage of autophagic flux in the late stage. Transcriptomics identified differences in mitophagy-related genes, and analysis of the levels of the corresponding proteins indicated that mitophagy in GBM cells was induced mainly through BNIP3L. Increased expression of BNIP3L disrupts the Bcl-2-Beclin-1 complex, thereby releasing Beclin-1 and activating autophagy. Autophagy was inhibited after silencing of BNIP3L and overexpression of Bcl-2 in GBM cells, and the growth inhibitory effect of DPD was significantly reduced. This result demonstrated that DPD induces mitophagy in GBM cells through BNIP3L. Finally, activation of incomplete mitophagy in GBM cells by DPD through BNIP3L in vivo was demonstrated by establishing a mouse subcutaneous xenograft tumor model. In this study, in vitro and in vivo experiments established that DPD inhibited GBM cell growth by inducing BNIP3L-mediated incomplete mitophagy, which provides an experimental basis for studying new treatments of GBM. Graphical Abstract